Choroidal neovascularization by active ocular toxoplasmosis: a case report - Ku Lozano, Jenny Kam Lin; Conde Obregon, Charles Gino; Ku Lu, Eduardo Maron; Samudio, Margarita (Medicina Clínica y Social, 2025)
A 33– year–old woman attended to the eye clinic with a 5-day history of decreased unilateral visual acuity with no previous medical history. Clinical-ophthalmological examination revealed an elevated macular lesion compatible with active ocular toxoplasmosis which was treated with both antibiotics and anti-VEGF therapy, with which the patient evolved favorably.